Intestinal microbiota in exclusively breast-fed infants with blood-streaked stools - Nevoral, Jiří; Rada, Vojtěch; Vlková, Eva; Bláhová, Květa; Bronský, Jiří; Bubáková, Daniela; Killer, Jiří (Folia microbiologica, 2009)
Intestinal microbiota in exclusively breast-fed infants with blood-streaked stools and in healthy exclusively breast-fed babies was compared. Total anaerobes, bifidobacteria, lactobacilli, coliform bacteria, enterococci and clostridia were quantified by cultivation methods in feces of 17 full-term exclusively breastfed patients (aged 16.3 +/- 7.4 weeks) with blood-streaked stools and in the control group of 22 healthy fullterm exclusively breast-fed infants (13.7 +/- 6.4 weeks). Specific fluorescence in situ hybridization kits for Bifidobacterium spp. were used for the quantitative detection of bifidobacteria in samples. Control samples had significantly (p < 0.05) higher counts of total anaerobes. Bifidobacteria were not detected in patients' samples in 65 % and in controls in 36 % (p < 0.01). Bifidobacteria counts were also significantly higher in the control group (p < 0.01). Furthermore, clostridia strains were detected only in feces from bifidobacteria-negative infants reaching counts >8 log CFU/g. Lactobacilli were not detected in 65 % patients and in 45 % control samples. However, this difference was not significant as well as the difference in lactobacilli counts. Eosinophilia was observed in 35 % of patients, low IgA concentration in 71 % and also low IgG concentration in 71 %. pANCA positivity was found in 53 % of patients. In conclusion a significant low proportion of bifidobacterial microbiota in patients with blood-streaked stools was shown in comparison with controls.
Keywords: kojení; Infant; feces; Humans; kojenec; střeva; imunoglobulin G; Intestines; Female; financování organizované; Financing, Organized; lidé; Immunoglobulin A; Feces; ženské pohlaví; Male; imunoglobulin A; Proctocolitis; Bacteria; proktokolitida; Breast Feeding; mužské pohlaví; Immunoglobulin G